The player and the character : building identity through game audio - Costa, Mariana Vieira de Melo (2017)
In spite of the increasing interest that video games have gained over the last decades, there has not yet been an academic effort to identify trend-like patterns in the creation of sound for video game characters. Such studies would be beneficial for amateur sound designers and indie game designers by enabling them to better understand the strategies that may coerce the player into diving and pleasantly navigating within the game world. The search for answers to this research gap entailed a path of research, which unfolded into six chapters. The Introduction (Chapter 1) describes the research gap and the mixed methods research that was used, while Chapter 2 contextualizes it. Chapter 3 seeks to understand the problem at the theoretical level, examining the concepts of Perception, Emotion and Immersion, and Chapter 4 delves into the research problem, aiming at evincing the importance of character soundprint for the acoustic ecology of the game. Chapter 5 confirms and further develops the previous research findings by investing in an in-depth analysis of two instrumental case studies. Finally, the Conclusion (Chapter 6) levels up the discussion, hinting at the new paths for game audio that Virtual Reality and 3-D audio will lead to. The dissertation offers a variety of research outputs that were essential for grounding the research hypothesis and which will hopefully be useful in the future: analytical graphs resulting from an online survey; a table systematizing the way different musical structures influence emotion; a table resulting from the direct observation of popular characters’ soundprints in a universe of 30 games; a table summarizing the soundprint types from patterns identified in the previous table; a table for structuring game analysis; and several tables analysing the case studies Non-Player Characters’ and Player Characters’s soundprints. Even though it is not an exact science, the analysis of video game characters showed it is possible to discern different soundprint types. The research further evinced that, along with the remaining structures of the game, sound and soundprints assist with the immersion process of the players, enhancing their opportunities for identifying with the characters and finding their own place in the game world.